Blood lactate diagnostics in exercise testing and training - Beneke, R.; Leithäuser, R. M.; Ochentel, O. (International Journal of Sports Physiology and Performance, 2011)
A link between lactate and muscular exercise was seen already more than 200 years ago. The blood lactate concentration (BLC) is sensitive to changes in exercise intensity and duration. Multiple BLC threshold concepts define different points on the BLC power curve during various tests with increasing power (INCP). The INCP test results are affected by the increase in power over time. The maximal lactate steady state (MLSS) is measured during a series of prolonged constant power (CP) tests. It detects the highest aerobic power without metabolic energy from continuing net lactate production, which is usually sustainable for 30 to 60 min. BLC threshold and MLSS power are highly correlated with the maximum aerobic power and athletic endurance performance. The idea that training at threshold intensity is particularly effective has no evidence. Three BLC-orientated intensity domains have been established: (1) training up to an intensity at which the BLC clearly exceeds resting BLC, light- and moderate-intensity training focusing on active regeneration or high-volume endurance training (Intensity < Threshold); (2) heavy endurance training at work rates up to MLSS intensity (Threshold < Intensity < MLSS); and (3) severe exercise intensity training between MLSS and maximum oxygen uptake intensity mostly organized as interval and tempo work (Intensity > MLSS). High-performance endurance athletes combining very high training volume with high aerobic power dedicate 70 to 90% of their training to intensity domain 1 (Intensity < Threshold) in order to keep glycogen homeostasis within sustainable limits.